Perencanaan Pajak dan Intensitas Aset Tetap terhadap Manajemen Laba: Agency Theory Perspective - Dian Sulistyorini Wulandari (JAAF (Journal of Applied Accounting and Finance), 2021)
This study aims to determine the effect of tax planning and the intensity of fixed assets on earnings management. This study uses secondary data. The population of this study are real estate, property and construction companies listed on the Indonesia Stock Exchange during the 2016-2018 period. It has a total of 81 companies. Purposive sampling technique is used in order to obtain a sample of 32 companies that meet the criteria. This study uses linear regression analysis with a significance level of 5%. The results showed that tax planning and asset intensity had no significant effect on earnings management.